EKSISTENSI MUHAMMADIYAH DALAM PERKEMBANGAN PENDIDIKAN INDONESIA - Hidayat, Syafri; Hudaidah, Hudaidah (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
Muhammadiyah as one of the Indonesian Islamic community organizations has evolved into an organization for the Indonesian education movement. This can be seen from the number of educational establishments that include the word Muhammadiyah in the name of the institution. Almost all over Indonesia there are Muhammadiyah schools. This social phenomenon raises several questions. Why are Muhammadiyah schools spread throughout Indonesia? What is the purpose of Muhammadiyah in building these schools?. This question is the problem formulation of this research. The purpose of this study is to determine the aims and objectives of the Muhammadiyah organization to become the pioneer of the Indonesian education movement during the colonial period to the reformation period. The method we use in this research is the historical method which includes the study of literature, records the actual data on the number of Muhammadiyah and non-Muhammadiyah schools, and compares and analyzes the data as the results and conclusions of this study. The conclusion obtained from this research is that Muhammadiyah has played an active role in educating the nation's life as the goal of the Indonesian nation, both during the colonial and post-proclamation periods with all of his policies. Muhammadiyah has become the motor for updating Indonesian education as an expression of K.H. Ahmad Dahlan towards the education sector during the colonial period. Muhammadiyah wants to provide a new perspective that education is holistic integrative, not in a partial dichotomous area, which can contribute to the development and progress of the nation.